The emerging field of radiomics in esophageal cancer: current evidence and future potential - van Rossum, Peter SN.; Xu, Cai; Fried, David V.; Goense, Lucas; Court, Laurence E.; Lin, Steven H. (Translational Cancer Research; Vol 5, No 4 (August 08, 2016): Translational Cancer Research (Focused Issue: Radiomics in Radiation Oncology), 2016)
‘Radiomics’ is the name given to the emerging field of extracting additional information from standard medical images using advanced feature analysis. This innovative form of quantitative image analysis appears to have future potential for clinical practice in patients with esophageal cancer by providing an additional layer of information to the standard imaging assessment. There is a growing body of evidence suggesting that radiomics may provide incremental value for staging, predicting treatment response, and predicting survival in esophageal cancer, for which the current work-up has substantial limitations. This review outlines the available evidence and future potential for the application of radiomics in the management of patients with esophageal cancer. In addition, an overview of the current evidence on the importance of reproducibility of image features and the substantial influence of varying smoothing scales, quantization levels, and segmentation methods is provided.